2003
DOI: 10.1080/713603185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genistein on the endometrium: ultrasonographic evaluation

Abstract: The aim of our study was to evaluate the effects of isoflavones on climacteric-related symptoms and on the endometrium in postmenopausal women, in a prospective, open, randomized, clinical trial performed at the Menopause Clinic of our Department. Seventy postmenopausal women were randomly assigned to two treatment groups receiving 12 cycles of treatment with genistein (group A) or calcium (group B). In all patients ultrasonographic endometrial thickness and Kupperman Index (KI) were evaluated at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Indeed, our study showed no difference in endometrial thickness between placebo, genistein, and EPT groups. This finding confirms and extends recent published data 30 showing that the administration of 36 mg/day of genistein for 12 months did not induce endometrial growth when compared with placebo; however, our data are, at least in our opinion, more impressive because we have administered a higher dose (54 mg/day of genistein) and the isoflavone effect was controlled versus both placebo and EPT. …”
Section: Discussionsupporting
confidence: 94%
“…Indeed, our study showed no difference in endometrial thickness between placebo, genistein, and EPT groups. This finding confirms and extends recent published data 30 showing that the administration of 36 mg/day of genistein for 12 months did not induce endometrial growth when compared with placebo; however, our data are, at least in our opinion, more impressive because we have administered a higher dose (54 mg/day of genistein) and the isoflavone effect was controlled versus both placebo and EPT. …”
Section: Discussionsupporting
confidence: 94%
“…Unfortunately, the results of many studies are inconsistent due to a lot of bias [18,19]. So far, there is low evidence for any well-defined estrogen-like or anti-estrogen-like effect in humans [20,21]. One possible reason for the apparently incoherent findings could be the quantitatively and qualitatively variable composition of phytoestrogens in food stuff and their complex metabolism with the synthesis of miscellaneous derivates which partially show diverse biologic activities.…”
Section: Classification Structure and Metabolism Of Isoflavonesmentioning
confidence: 87%
“…In contrast, RCTs invariably show no proliferative effect of isoflavones on the postmenopausal endometrium, regardless of the isoflavone source and dose (summarized in Table 5). 16,[41][42][43][44][45][46]57,58 From the clinical and epidemiological studies, one can hypothesize that isoflavones have an inert effect on the endometrium, similar to raloxifene 10 or that isoflavones have an antiproliferative effect on the meno- Menopause, Vol. 10, No.…”
Section: Discussionmentioning
confidence: 98%